Enhancement of broad-spectrum disease resistance in wheat through key genes involved in systemic acquired resistance - Zhao, Shuqing; Li, Mengyu; Ren, Xiaopeng; Wang, Chuyuan; Sun, Xinbo; Sun, Manli; Yu, Xiumei; Wang, Xiaodong (Frontiers in Plant Science, 2024)
Systemic acquired resistance (SAR) is an inducible disease resistance phenomenon in plant species, providing plants with broad-spectrum resistance to secondary pathogen infections beyond the initial infection site. In Arabidopsis, SAR can be triggered by direct pathogen infection or treatment with the phytohormone salicylic acid (SA), as well as its analogues 2,6-dichloroisonicotinic acid (INA) and benzothiadiazole (BTH). The SA receptor non-expressor of pathogenesis-related protein gene 1 (NPR1) protein serves as a key regulator in controlling SAR signaling transduction. Similarly, in common wheat (Triticum aestivum), pathogen infection or treatment with the SA analogue BTH can induce broad-spectrum resistance to powdery mildew, leaf rust, Fusarium head blight, and other diseases. However, unlike SAR in the model plant Arabidopsis or rice, SAR-like responses in wheat exhibit unique features and regulatory pathways. The acquired resistance (AR) induced by the model pathogen Pseudomonas syringae pv. tomato strain DC3000 is regulated by NPR1, but its effects are limited to the adjacent region of the same leaf and not systemic. On the other hand, the systemic immunity (SI) triggered by Xanthomonas translucens pv. cerealis (Xtc) or Pseudomonas syringae pv. japonica (Psj) is not controlled by NPR1 or SA, but rather closely associated with jasmonate (JA), abscisic acid (ABA), and several transcription factors. Furthermore, the BTH-induced resistance (BIR) partially depends on NPR1 activation, leading to a broader and stronger plant defense response. This paper provides a systematic review of the research progress on SAR in wheat, emphasizes the key regulatory role of NPR1 in wheat SAR, and summarizes the potential of pathogenesis-related protein (PR) genes in genetically modifying wheat to enhance broad-spectrum disease resistance. This review lays an important foundation for further analyzing the molecular mechanism of SAR and genetically improving broad-spectrum disease resistance in wheat.